2012
DOI: 10.4104/pcrj.2011.00079
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of using bronchial hyperresponsiveness to manage asthma in primary care: a pilot study

Abstract: Aims: To determine if indirect testing for bronchial hyperresponsiveness (BHR) to monitor inhaled corticosteroid (ICS) treatment in asthma is feasible and acceptable in primary care.Methods: Fourteen adult patients with asthma aged 22-70 years (4M:10F, forced expiratory volume in 1 s >70% predicted) taking ICS performed a test for BHR using mannitol on three visits 6 weeks apart. ICS dose adjustments were made based on the presence of BHR. The Asthma Quality of Life Questionnaire (AQLQ) and the Asthma Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Their qualitative analyses revealed increased understanding of the chronic nature of asthma and improved involvement in goal-setting between patients and their primary care health professional. Interestingly, these qualitative data 2 were gathered from BHR-positive patients, which casts some doubt on the external validity of the findings. As with many studies on asthma management in primary care, patients recruited into studies are already highly motivated and compliant.…”
Section: Editorialsmentioning
confidence: 97%
See 4 more Smart Citations
“…Their qualitative analyses revealed increased understanding of the chronic nature of asthma and improved involvement in goal-setting between patients and their primary care health professional. Interestingly, these qualitative data 2 were gathered from BHR-positive patients, which casts some doubt on the external validity of the findings. As with many studies on asthma management in primary care, patients recruited into studies are already highly motivated and compliant.…”
Section: Editorialsmentioning
confidence: 97%
“…In this issue of the PCRJ, Turton et al 2 have completed an important pilot study exploring the use of point-of-care indirect bronchial hyperresponsiveness (BHR) testing with mannitol in order to monitor and (importantly) adjust the ICS dose. Despite the small numbers, the authors found that there were improvements in Asthma Quality of Life Questionnaire (AQLQ) scores that correlated with improvements in BHR after increases in ICS dosage.…”
Section: Editorialsmentioning
confidence: 99%
See 3 more Smart Citations